Socioeconomic Status and Healthcare Support on Anti-Tuberculosis Medication Adherence Among Pediatric Tuberculosis Patients - Sari, Nissa Prima (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2025)
Background: Tuberculosis (TB) remains a major public health challenge, particularly among children in low- and middle-income countries. Adherence to anti-tuberculosis (anti-TB) medication is essential for treatment success, but socioeconomic factors and healthcare support significantly influence adherence rates. This study examines the association between socioeconomic status (SES), healthcare support, and medication adherence among pediatric TB patients in Solok, West Sumatera, Indonesia. Methods: A cross-sectional study was conducted involving 57 pediatric TB patients. Data on SES, healthcare support, and medication adherence were collected through structured caregiver interviews and medical record reviews. Statistical analysis included Chi-square to identify factors influencing adherence. Results: The study found that 73.7% of pediatric TB patients were adherent, while 26.3% were non-adherent. Children from higher SES backgrounds were 3.5 times more likely to adhere to treatment (OR = 3.5; 95% CI: 1.8–6.8, p = 0.003). Additionally, those receiving better healthcare support were 2.8 times more likely to adhere (OR = 2.8; 95% CI: 1.5–5.2, p = 0.041). Conclusion: Socioeconomic status and healthcare support significantly impact anti-TB medication adherence among pediatric patients. Strengthening health policies, financial support, and community-based healthcare programs can improve adherence rates and treatment outcomes. Public health strategies should focus on targeted interventions for low-income families to reduce treatment default rates.